Petani Tambak Ikan Bolu di Desa Teppo`e Kecamatan Poleang Timur - Nirmalasari Nirmalasari; Hasniah Hasniah (JURNAL KABANTI: Kerabat Antropologi, 2023)
Teppo`e Village is one of the famous sponge-producing areas in Bombana Regency. But the condition of the supply of sponge fish from members of the sponge cultivation group is often disrupted because the farmers face serious problems in the management of the maintenance of sponge fish. The purpose of this study was to determine the problems faced by sponge fish farmers in Teppo`e Village, Poleang Timur District, Bombana Regency, as well as to determine the strategies of pond farmers in overcoming problems in pond management. This study uses the theory of Adaptation Strategy According to John W. Bennett. Data collection Teppo'e Village, Poleang Timur District, Bombana Regency, especially sponge fish farmers experienced problems in pond management, including: (1) Damage to Pematang Empang, (2) Lack of Capital, (3) Lack of fertilizer. To overcome this problem, pond farmers have several strategies, including (1) Pematang Improvement, (2) Borrowing Business Capital, (3) and Switching Vename Shrimp Farms. This is done so that the pond farmers can continue their aquaculture business